2015
DOI: 10.1016/j.pepi.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Thermal evolution of the core with a high thermal conductivity

Abstract: The rate at which heat is extracted across the core mantle boundary (CMB) is constrained by the requirement of dynamo action in the core. This constraint can be computed explicitly using the entropy balance of the core and depends on the thermal conductivity, whose value has been revised upwardly. A high order model (fourth degree polynomial of the radial position) for the core structure is derived and the implications for the core cooling rate and thermal evolution obtained, using the recent values of the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
271
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(293 citation statements)
references
References 104 publications
(221 reference statements)
11
271
0
Order By: Relevance
“…prior to inner core formation, after which Q cmb is set constant to ensure the outer core remains just superadiabatic. Results from other recent studies are shown in yellow 68 , pink 63 , orange 80 and maroon 69 . The inverted triangle denotes that ∆ρ did not enter into this formulation.…”
Section: Core Dynamics and Evolution With High Conductivitiesmentioning
confidence: 65%
See 2 more Smart Citations
“…prior to inner core formation, after which Q cmb is set constant to ensure the outer core remains just superadiabatic. Results from other recent studies are shown in yellow 68 , pink 63 , orange 80 and maroon 69 . The inverted triangle denotes that ∆ρ did not enter into this formulation.…”
Section: Core Dynamics and Evolution With High Conductivitiesmentioning
confidence: 65%
“…Recent calculations with the new (high) conductivities find that 1) The inner core age is less than 500-600 Ma 24,59,63,80 ; 2) high early CMB heat flow and corresponding core temperatures that significantly exceeded present estimates of the lower mantle solidus temperature 59,63,68,94 imply partial melting of the lowermost mantle in the past; 3) the present-day core is subadiabatic at the top and may be stably stratified 24,26,80 . Prior to the high conductivity estimates, models predicted inner core nucleation 1 billion years ago 8 , early core temperatures comparable to the lower mantle solidus 9 , and superadiabatic conditions throughout the core at the present-day.…”
Section: Core Dynamics and Evolution With High Conductivitiesmentioning
confidence: 93%
See 1 more Smart Citation
“…The present day geodynamo is mainly driven by compositional buoyancy, due to light element release by the crystallisation of the inner core. A core with large thermal conductivity (e.g., Pozzo et al, 2012;Ohta et al, 2016) yields a young age (less than 1 Gyr) for the inner core (Labrosse, 2015;Nimmo, 2015a), which is in apparent contradiction with palaeomagnetic evidence for an old geodynamo dating back to at least 3.5 Ga (Tarduno et al, 2010). Even with a low core thermal conductivity (Konôp-ková et al, 2016), the problem is partially mitigated, in that a dynamo can be sustained for 3.5 Gyr (e.g., Labrosse, 2003;Nimmo, 2015a), but initial core temperatures are very high, above 7000 K, which implies a fully molten Earth for extended periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…Because radionuclide abundance decreases with time, the process is dominant very early in Earth's history and vanishes with time. Potassium and uranium are the main sources of heat in the Earth, and their incorporation in the core has been thoroughly examined through the years (e.g., Buffett, 2002;Gubbins et al, 2003;Labrosse, 2003Labrosse, , 2015Nimmo et al, 2004), and it was shown that the incorporation of ~100s of ppm K in the core would mitigate the young inner core/early geodynamo/hot initial core conundrum.…”
Section: Introductionmentioning
confidence: 99%